Fitotoxicidade e excreção radicular do glifosato por soja transgênica em diferentes solos e níveis de fósforo - Casonatto, Marilza da Silva (2014)
Genetic modifications brought a significant increase in the utilization of glyphosate, with successive applications. Although the transgenic soybean having its resistance mechanism, it has been suffering some injuries along with non-targeted plants. The glyphosate can suffer root excretion from the target plant, and it can be adsorbed by the non-target one. This study intends to evaluate the root excretion and the phytotoxicity suffered by the glyphosate in genetic modified soybean in different soil types and phosphorus levels. Was cultivated for thirty days, a soybean plant (target plant) and corn (non-target plant) in pots with two soils, Red-Yellow Latosol and Quartzarenic Neosol, which received: one, two and three times the maintenance dose of fertilization of phosphorus, only in the soybean plants, six doses of glyphosate (0, 1, 2, 10, 50 and 100 recommended dose). Glyphosate was applied only in the soybean. The maize plants were completely isolated. The experimental design was completely randomized, in factorial design: 2 x 6 x 3 x 3 that being two soil types, six glyphosate doses, three evaluation periods and three phosphorus doses, with four replications. Evaluated at six hours, three and ten days after application (DAA), the developmental characteristics of corn plants: plant height, chlorophyll a and b, phytotoxicity, and at 10 DAA it was also evaluated wet and dry biomass of the shoots of both the corn and the soybean plants, and dry biomass of the roots of both the corn and the soybean plants. The phytotoxicity varied directly with the glyphosate doses, being superior the effects on the Red-Yellow Latosol) soil with less phosphorus; the rest of the characteristics decreased with the increase of the doses.